Infância, docência e Tecnologias Digitais de Informação e Comunicação (TDIC's): formação do professor de educação infantil - Silva, Luciana Maria da (2018)
The present work includes the formation of the teacher of Early Childhood Education, together with the emergence and recognition of Early Childhood Education (LDB 9394/96) under the optics history and social. This training of the teacher appears as a controversial subject, mainly thinking about the destinies of the children. A serious revision is necessary in the teacher education curriculum, where it will question the real role that education plays in society, the true scientific and social function of the teacher, among others. Lack of interest or over-indulgence, or too many ordinances or resolutions away from a real society, are not the best ways. The main objective of the work is to study, to know and to discuss how the formation of the Infantile Education teacher has occurred, historically and socially, taking into account the contemporary world in front of the TDIC'S. It aims to analyze and understand the importance of the uses of TDIC'S. It aims to analyze and understand the importance of the use of TDICs as a facilitator of the teaching-learning process in the pedagogical making of the teacher of Early Childhood Education. Therefore, it is based on two basic problems: 1 - How, historically and socially, does the formation of the Infantile Education teacher to attend to the contemporary world in front of the TDICs? 2 - Can TDICs be used as facilitators of the teaching-learning process in the pedagogical making of the teacher of Early Childhood Education? The work shows that the teacher currently adopts a new posture, a new role: mediator between the child and the world, with the family as a co-participant in the teaching-learning process. The pre-school ceases to be a place of hygiene care and becomes an educational space. The bibliographical research was the methodology of work chosen, highlighting some authors as: Ariès, P .; Baccega, M.A .; Badinter, E .; Barbosa, P.A .; Murarolli, P.L .; Barreto, Angela Maria Rabelo Ferreira; Vigneron, Jaques; Oliveira, Vera B.